2021
DOI: 10.1155/2021/5511221
|View full text |Cite
|
Sign up to set email alerts
|

Carica papaya L. Leaf: A Systematic Scoping Review on Biological Safety and Herb-Drug Interactions

Abstract: Introduction. The Carica papaya L. leaf is gaining interest as a potential therapeutic agent for alleviating dengue- and non-dengue-associated thrombocytopaenia. In that regard, safety considerations are as important as efficacy potential. The safety evaluation of botanical products for human use is complicated by variable formulations, complex phytochemical composition, and extrinsic toxicants. This review aimed to systematically collate related safety clinical and preclinical data, as well as reports on herb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…In conclusion, papaya leaf consumption by adults is most likely safe for short-term use, but should be carefully managed when it is given to pregnant women and people with liver impairments. Furthermore, potential herb-drug interactions could occur with oral hypoglycaemic agents, P-glycoprotein substrates, and antibiotics with cation-chelating properties [133]. As previously mentioned, a papaya leaf extract produced by Sido Muncul showed non-sub-chronic toxicity even for long periods of consumption when it was evaluated in an animal study.…”
Section: Safetymentioning
confidence: 96%
“…In conclusion, papaya leaf consumption by adults is most likely safe for short-term use, but should be carefully managed when it is given to pregnant women and people with liver impairments. Furthermore, potential herb-drug interactions could occur with oral hypoglycaemic agents, P-glycoprotein substrates, and antibiotics with cation-chelating properties [133]. As previously mentioned, a papaya leaf extract produced by Sido Muncul showed non-sub-chronic toxicity even for long periods of consumption when it was evaluated in an animal study.…”
Section: Safetymentioning
confidence: 96%
“…Scientific studies have demonstrated the use of papaya for its anti-bacterial, anti-inflammatory, nephroprotective, antiparasitic, antidiabetic, hepatoprotective, and anti-dengue properties [ 13 ]. Although comprehensive investigation on the bioactive compounds is needed to understand the mechanism of action, positive conclusions are reported from various studies to validate the use of papaya leaves for the dengue fever treatment and have shown effectiveness in refining thrombocytopenia using in-vitro and in-vivo systems [ 14 ]. Multiple small-scale studies and case reports suggest a rapid increase of platelet count in the patients after management of papaya leaf extract and attribute its erythrocyte membrane-stabilizing potential as a possible reason for this effect [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although comprehensive investigation on the bioactive compounds is needed to understand the mechanism of action, positive conclusions are reported from various studies to validate the use of papaya leaves for the dengue fever treatment and have shown effectiveness in refining thrombocytopenia using in-vitro and in-vivo systems [ 14 ]. Multiple small-scale studies and case reports suggest a rapid increase of platelet count in the patients after management of papaya leaf extract and attribute its erythrocyte membrane-stabilizing potential as a possible reason for this effect [ 14 , 15 ]. Direct antiviral activity has been demonstrated in the in-vitro studies wherein THP-1 cells treated with papaya leaves extract (PLE) showed a significant decrease in DENV envelope and NS1 protein expression, decreased viral load, and an increase in the expression of Type I interferons (IFN-α) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 9 Additional studies on post-chemotherapy populations have mirrored the results of these studies and have found no treatment-related adverse events; however, a recent review has reported that the most common side effect of CPLE use is minor gastrointestinal disturbance. 10 , 11 Recently, a case report of a neonate with persistent refractory thrombocytopenia concluded that CPLE treatment may even be applicable in this population. 12 …”
Section: Introductionmentioning
confidence: 99%